Sistem Alert Warning Monitoring Masa Tenggang Kontrak - Rheza Pratama; Muhammad Irwan Padli Nasution (AI Society & STMIK Indonesia, 2022)
PT Superintending Company of Indonesia (Persero) (referred to as SUCOFINDO) is a State-Owned Enterprise established between the Government of the Republic of Indonesia and SGS. At this time PT. Sucofindo (Persero) cooperates a lot with other companies, a total of 3458 external supply companies are active in the procurement of goods and services, so that often employees in the general function section have problems remembering the time of the cooperation contract. At this time the general function is still using the system in a way where employees still have to manually input data from every activity of procurement of goods and services in Microsoft Excel. the system used is deemed less effective and efficient, making it difficult to obtain information on a procurement contract. This research was conducted to facilitate the monitoring of a contract. The system uses the PHP programming language and MySQL database. The results of this study are a web-based monitoring information system that provides warning alerts if the contract is in the grace period, as well as providing other information about the stages of the process that have been carried out in a contract.